2013
DOI: 10.1371/journal.pone.0082200
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Maternal Long-Term Hypoxia: Acclimatization Responses with Altered Gene Expression in Ovine Fetal Carotid Arteries

Abstract: In humans and other species, long-term hypoxia (LTH) during pregnancy can lead to intrauterine growth restriction with reduced body/brain weight, dysregulation of cerebral blood flow (CBF), and other problems. To identify the signal transduction pathways and critical molecules, which may be involved in acclimatization to high altitude LTH, we conducted microarray with advanced bioinformatic analysis on carotid arteries (CA) from the normoxic near-term ovine fetus at sea-level and those acclimatized to high alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…In previous studies, we have described this technique in detail (2325). Microarray analysis was conducted by utilizing the commercial services of GenUs BioSystems (Northbrook, IL).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we have described this technique in detail (2325). Microarray analysis was conducted by utilizing the commercial services of GenUs BioSystems (Northbrook, IL).…”
Section: Methodsmentioning
confidence: 99%
“…for hypoxic fetal and placental weights, respectively). Recent reports have shown that LTH alters endocrine, vascular, and pulmonary physiology in the fetus (11,31,39). For this reason, we studied the effect of LTH on placental and fetal expression of vitamin D metabolic, transport, and receptor genes.…”
Section: Role Of Lth On Placental and Fetal Expression Of Vitamin D-rmentioning
confidence: 99%
“…shown that normoxic and hypoxic pregnancies have similar outcomes but altered physiological adaptations (11,31,39). To assess the vitamin D status in this model, we analyzed the plasma levels of vitamin D metabolites [cholecalciferol, 25-OH-D, and 1␣,25-(OH) 2 D] in nonpregnant and pregnant ewes and their fetuses at normoxia (NMX; sea level) and long-term hypoxia (LTH; 3,800 m above sea level).…”
Section: Effect Of Pregnancy and High-altitude Long-term Hypoxia On Vmentioning
confidence: 99%
See 2 more Smart Citations